Barriers to Successful Health Information Exchange Systems in Canada and the USA: A Systematic Review - Almoaber, Basmah; Amyot, Daniel (Université d'Ottawa | University of Ottawa, 2017)
Background: Despite the potential benefits of health information exchange (HIE) and the two decades of efforts from the Canadian and the American governments to promote health exchange projects, failures far outnumber successes. Objective: To better understand the barriers influencing the adoption and implementation of inter-organization HIE systems in Canada and the USA. Method: A systematic literature review was conducted to examine English-language studies that identified barriers to HIE in Canada and the USA between 1995 and 2016. Electronic databases, backward searching and expert consultations were used. Results: 31 articles have been included. There is a dearth of publications reported on the HIE barriers in Canada. A total of 33 barriers have been identified. Conclusion: There are noticeable differences in the barriers reported in these countries. Privacy concerns and a lack of stakeholder buy-in are recurring barriers over time in the USA. Low adoption of electronic medical records is the main barrier in Canada.
Keywords: Barriers; Canada; Health Information Exchange; HIE; Literature Review; Privacy; USA